Management of Endo-perio Lesion by Guided Tissue Regeneration: A Case Report - Abhaya Chandra Das1, Sourav Panda1, Manoj Kumar1, Gatha Mohanty2, Utkalika Das3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
To diagnose and to treat, is a crucial part of management of an endo-perio lesion. The sign and symptomsof endo-perio lesion are difficult to accountable for a general dental surgeon. For that reason, it needs moredetailed examination and definite treatment plan. The outcomes of endo-perio lesion are highly unpredictabledue its multiple etiological factors. The primary and secondary etiological factors of endo-perio lesionsmay have numerous variation and ultimately concludes the definite treatment plan complex. A 43-year-oldfemale patientcame to Department of Periodontics, with a chief complaint of pain in right posterior lowertooth region.On clinical examination, there was 5mm of periodontal pocket, occlusal restoration in 47. Thetreatment plan was made as first endodontic treatment followed by periodontal treatment. So endodontictreatment was carried out first in 47 after oral prophylaxis. Then under local anesthesia, open debridementwas done in 47 and bone graft was placed in the defect. Resorbable membrane was placed over the graft.Suture was placed and periodontal dressing was given and followed up to 9 months. She was very satisfiedwith the result.